Location and the Multinational Enterprise: A Neglected Factor? - Dunning, John H. (Journal of International Business Studies, 1998)
This article first traces the changing world economic scenario for international business over the past two decades, and then goes on to examine its implications for the location of foreign direct investment and multinational enterprise activity. It suggests that many of the explanations of the 1970s and early 1980s need to be modified as firm-specific assets have become mobile across natural boundaries. A final section of the article examines the dynamic interface between the value-added activities of multinational enterprises in different locations.